Long‐term patient satisfaction after retropubic and transobturator mid‐urethral slings for female stress urinary incontinence. Issue 9 (8th June 2016) - Al‐Zahrani, Ali A.; Gajewski, Jerzy
Abstract: Aim: The aim of this study was to report long‐term patient outcomes after retropubic and transobturator mid‐urethral slings for female stress urinary incontinence. Methods: Women who underwent mid‐urethral sling for stress urinary incontinence between 2000 and 2010 were invited to participate in a survey regarding their overall improvement. Patients' outcomes were assessed using the International Consultation on Incontinence Questionnaire – Short Form and the Global Response Assessment Scale. Results: The questionnaires were completed by 330 patients. Their median age at the time of surgery was 54.8 years (±12.9) and the median follow‐up period was 11.9 years (±6.4). Retropubic and transobturator approaches were performed in 128 (38.8%) and 202 (61.2%) patients, respectively. The International Consultation on Incontinence Questionnaire – Short Form score dropped from an average of 14 (±4.1) to 6.4 (±6) with no significant difference between the two groups. The Global Response Assessment Scale showed an 9% greater improvement in the retropubic (66.4%) over the transobturator (57.4%) approach. De novo overactive bladder was the commonest long‐term reported adverse event, affecting 18/330 patients (5.5%). Voiding dysfunction that required surgical correction following the retropubic approach occurred in three patients (2.3%). Conclusion: Mid‐urethral slings for the management of female stress urinary incontinence had good and durable long‐term effects. Although the retropubic approach gave better results, they were not significantly different than those of the transobturator approach.